Sequentially regular polymer acceptors featuring flexible spacers for high-performance and mechanically robust all-polymer solar cells. Issue 11 (29th September 2022) - Lee, Jin-Woo; Sun, Cheng; Lee, Sun-Woo; Kim, Geon-U.; Li, Sheng; Wang, Cheng; Kim, Taek-Soo; Kim, Yun-Hi; Kim, Bumjoon J.
Abstract : We report a new molecular design of sequentially regular polymerized small-molecule-acceptors containing flexible spacer (FS) units (PYFS-Reg) to achieve all-polymer solar cells with both high-performance and mechanical stretchability. Abstract : Developing high-performance and mechanically robust polymer solar cells (PSCs) is crucial for realizing wearable power sources. While efficient all-polymer solar cells (all-PSCs) can be fabricated from polymerized small-molecule acceptors (PSMAs) with high optical absorption and electron mobilities, they still show limited mechanical robustness. Here, we achieve highly efficient and mechanically robust all-PSCs by designing a PSMA (PYFS-Reg) containing sequence-regular flexible spacers (FSs). The regular incorporation of the FS units into PSMAs is essential in simultaneously improving the electrical and mechanical properties of blend films. As a result, all-PSCs featuring PYFS-Reg achieve a high power conversion efficiency (PCE = 16.1%) and stretchability (crack onset strain (COS) = 22.4%), outperforming PSMAs without FSs ( i.e., PYBDT, PCE = 12.6% and COS = 11.7%) or with randomly distributed FSs ( i.e., PYFS-Ran, PCE = 12.2% and COS = 18.1%). Importantly, these all-PSCs are fabricated by an environmentally benign, non-halogenated solvent process. To further demonstrate their feasible applications in wearable devices, we construct intrinsically stretchable (IS) all-PSCs by using PYFS-Reg-based active layers, which exhibit a high PCE (10.6%) and excellent device stretchability (strain at PCE80% = 36.7%).